The Impact of Digital Technology on Private School Performance in Yenagoa, Bayelsa State - Olufunke, Adebayo P; Spring, Jokori-James Azibator (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
The majority of research on digital technology and business performance that has been conducted thus far focuses on enterprises, while little or no attention has been given to private schools in the local context, such as Yenagoa, Bayelsa state. Many works highlight digital literacy challenges among staff and students globally, but little has been done to assess the extent of these challenges within private schools in Yenagoa, where shifting client preferences, inadequate service quality, low staff engagement, organisational inefficiencies, infrastructure, training, and support systems may be uniquely constrained. This study addresses these issues by investigating the impact of digital agility on employee satisfaction and the influence of digital transformation on service quality. The study employed a quantitative case study design using stratified sampling, with 196 questionnaires distributed and 178 valid responses collected (90.8% response rate) from staff of top private schools in Yenagoa. Data were analysed using SPSS for descriptive statistics and Partial Least Squares Structural Equation Modelling (PLS-SEM) for inferential analysis. Validity and reliability were ensured through expert review, factor analysis, and Cronbach’s alpha (≥0.7). The findings revealed that digital agility has a significant positive effect on employee satisfaction, with a path coefficient of 0.911 and an R² of 0.830, indicating that it explains 83% of the variance. Similarly, digital transformation demonstrated a nearly perfect influence on service quality, with a path coefficient of 0.997 and an R² of 0.993, suggesting that advancements in digital capabilities substantially enhance both employee satisfaction and overall school performance.